1994
DOI: 10.1016/0304-3959(94)90111-2
|View full text |Cite
|
Sign up to set email alerts
|

The pain beliefs and perceptions inventory: further evidence for a 4-factor structure

Abstract: This study employed the Pain Beliefs and Perceptions Inventory (PBPAI) (Williams and Thorn 1989) with a German sample (n = 193) of pain patients. The original version has 3 subscales: (1) self-blame (S-B), (2) perception of pain as mysterious (MYST), and (3) beliefs about the temporal stability of pain (TIME). Item statistics, factor structure, and discriminant validity are reported. Factor analysis favored a 4-factor structure and replicated a finding by Strong et al. (1992). The TIME scale can be subdivided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
6

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 9 publications
4
27
0
6
Order By: Relevance
“…Although PBPI permanence showed significant bivariate correlations with pain measures, it failed to enter as significant in the final models. On the basis of similar observations, Herda et al 39 suggest it may be more difficult for individuals to cope with the constant experience of pain than to accept the idea that pain will be a long term, albeit intermittent problem.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although PBPI permanence showed significant bivariate correlations with pain measures, it failed to enter as significant in the final models. On the basis of similar observations, Herda et al 39 suggest it may be more difficult for individuals to cope with the constant experience of pain than to accept the idea that pain will be a long term, albeit intermittent problem.…”
Section: Discussionmentioning
confidence: 93%
“…14,21 The finding that greater endorsement of the belief that pain is a constant and enduring experience (eg, ''it seems like I wake up with pain and I go to sleep with pain,'' ''my pain varies in intensity but is always with me'') was associated with higher pain intensity and pain interference is compatible with previous studies of people with chronic pain as a primary condition. Several investigators have shown that beliefs about the stability or constancy of pain are positively associated with higher pain intensity, 19,37,39,53 greater psychologic distress, 37,39 and poorer physical functioning. 19,39 Stroud et al 20 similarly found that pain constancy beliefs were positively associated with greater pain interference among 163 people with heterogenous chronic pain conditions, even after controlling for the influence of demographic variables, pain severity, and work status.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Les résultats de notre procédure de validation attestent de la stabilité de la structure du construit mesuré par le PBPI dans sa version française. Autrement dit, la structure en quatre sous-échelles mesurée par le PBPI demeure très proche de celles mises en évidence lors de recherches effectuées auprès d'échantillons relativement comparables [5,6,9]. Notons toutefois que les diverses analyses effectuées nous ont conduits à réaffecter un item de la dimension pérennité dans la dimension mystère 1 et à supprimer un item de la dimension pérennité 2 .…”
Section: Cadre Et Objectifunclassified
“…La première classe comprend uniquement le score brut (3), la deuxième classe le score (4), la troisième classe le score (5), la quatrième classe le score brut (6). Seule la cinquième classe comporte un intervalle entre des scores bruts (6-12) reflétant bien le fait que très peu de patients ont un score élevé de culpabilité.…”
Section: Résultatsunclassified